Exploring Experimental Publishing: Mappings, Pilots, and Guidelines - Adema, Janneke (Septentrio Conference Series, 2021)
See RECORDING. This talk will provide an overview of the research on experimental publishing and reuse currently being conducted by the COPIM (Community-led Open Publication Infrastructures for Monographs) project, where we are exploring ways to more closely align existing software, tools and technologies, workflows and infrastructures for experimental publishing with the workflows of open access book publishers. Our research looks at experiments with the book that reimagine the relationalities that constitute academic writing, research, and publishing, and that speculate on what the future of the book and the humanities could look like beyond the printed codex-format as the standard publication choice. This talk will introduce the experimental book Pilot Projects we have co-initiated, and it will discuss our research on situating, and mapping experimental books and open source publishing tools and platforms for experimental book publishing. Finally, this talk will provide recommendations and guidelines to promote interaction around open access books.